Egg Production and Calcium-Phosphorus Utilization of Laying Hens Fed Diets Supplemented with Phytase Alone or in Combination with Organic Acid - Sari, Mustafa; Onol, Ahmet G.; Daskiran, Mehmet; Cengiz , Ozcan (International Journal of Poultry Science, 2012)
An experiment was conducted to determine the effects of dietary organic acid and phytase supplementation on performance and calcium and phosphorus utilization in laying hens. Two hundred 23-wk-old Brown Nick layers were randomly allocated into 50 cages (42 x 50 cm) each containing 4 birds. Each dietary treatment had 5 replications and each replication comprised two adjacent cages. Corn-soybean meal based rations were used. Five dietary treatments were formed as followed: (1) a basal ration with no supplemental P (negative control, NC) (2750 kcal ME/kg, 17% CP, 0.34% total P, 3.8% Ca), (2) basal ration supplemented with dicalcium phosphate (1.4%) (positive control, PC), (3) basal ration supplemented with 0.035% phytase (ZY Phytase II-5, NC+P), (4) basal ration supplemented with 1.0% organic acid (Salstop SD, NC+OA) and (5) basal ration supplemented with both 0.035% phytase and 1.0% organic acid (NC+POA). Water and feed were provided for ad libitum consumption and a lighting program of 16 h light : 8 h dark was applied throughout the study. NC treatment resulted in body weights that were lower (p<0.05) than those of hens fed diets supplemented with phytase, organic acid, or both. Hens fed diets supplemented with dicalcium phosphate, phytase and organic acid and phytase had higher egg production (p<0.001) (91.3, 86.1 and 93.7% respectively) compared to hens fed either basal diet (78.5%) or basal diet with organic acid supplementation (78.6%). Additionally, the unsupplemented or organic acid supplemented diet had lower FI and higher FCR (p<0.01). Hen tibia ash and serum calcium levels were not affected by the dietary treatments whereas diets supplemented with dicalcium phosphate, phytase and phytase + organic acid had higher (p<0.01) serum inorganic phosphorus. The results of this study indicate that dietary phytase improves P utilization in corn-soybean meal based diets with no supplemental P and acidification of gastrointestinal tract may further improve this utilization.